MANAJEMEN LABA DITINJAU DARI BEBAN PAJAK TANGGUHAN, PERENCANAAN PAJAK, LEVERAGE DAN UKURAN PERUSAHAAN: STUDI META ANALISIS - Winnica Maitri; Carmel Meiden (Jurnal Akuntansi, 2022)
This study aims to integrate research results related to the topic of deferred tax expense, tax planning, leverage and company size on earnings management in Indonesia for the 2015-2021 period. The topic of the effect of deferred tax expense, tax planning, leverage and company size on earnings management has been widely discussed, researched and still exist today, but existing research provides consistent and inconsistent results with different levels of significance. The data collection method used the observation method and the sample used in this study was 20 research journals. The sampling technique is purposive sampling technique. Researchers use meta-analysis to integrate research results and show conclusions related to the effects of deferred tax expense, tax planning, leverage and firm size on earnings management. The results of this study indicate that deferred tax expense, tax planning, leverage and firm size affect earnings management. In addition, this study also proves that the validity of agency theory in the 2015 - 2021 research period.